RELATIONSHIP OF FAMILY SUPPORT WITH ELDERLY LIVELINESS TO COME TO ELDERLY POSYANDU (STUDIED IN ELDERLY POSYANDU OF VILLAGE PLANDAAN AT JOMBANG) - Diah Ayu Anggraini; Arif Wijaya; Bambang Tutuko (Jurnal Keperawatan, 2013)
Livelines is frequency in visiting upon activity Posyandu in range of time one year.The purpose of this research was to know the relationship of family support with elderly liveline to come to elderly Posyandu in village of Plandaan Jombang. This research design used was analitic approach crossectional. The population of this research were the entire elderly in village of Plandaan as many as 120 people when this research was conducted. Sample of this research were 30 respondents. Sampling technique used was simple random sampling. IndependentVariabel was family support and the elderly liveliness was dependent variabel. The Instruments was a questionare.Statistical test use the Spearman Rho. The result known that the family support is in a good category is as big as 60% , big enough is 40%, while for elderly liveline is in a high category as long as 53,3%, and low category is 46,7%. Based on statistical test was obtained ρ value = 0,00, ρ< α, (α: 0,05), it means H1 accepted. The conclusion that there is the relation of family support with elderly livelines to come to elderly Posyandu in village of Plandaan Jombang.